Disrupting Science : Social Movements, American Scientists, and the Politics of the Military, 1945-1975 - Moore, Kelly, 1962- (Book collections on Project MUSE., 2008)
In the decades following World War II, American scientists were celebrated for their contributions to social and technological progress. They were also widely criticized for their increasingly close ties to military and governmental power--not only by outside activists but from among the ranks of scientists themselves. Disrupting Science tells the story of how scientists formed new protest organizations that democratized science and made its pursuit more transparent. The book explores how scientists weakened their own authority even as they invented new forms of political action. Drawing exten.